Finding the best versions of schedule for order fulfillment at food companies - Hrybkov, Serhii; Kharkyanen, Olena; Gladka, Yuliya (My University, 2020)
The article suggests a mathematical model of the multicriteria problem of formation of production tasks and operational-calendar plans at food companies, taking into account their specific features. The research was carried out, the bat algorithm and its modifications were adjusted and tested. The choice of the bat algorithm based on the Levy flight random search strategy is substantiated. This approach provides the formation of new and alternative plans for orders fulfillment at a food company, taking into account the proposed mathematical model.
Keywords: mathematical model; математична модель; the bat algorithm; алгоритм кажанів; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки